A qualitative exploration of the enablers of and barriers to conformance with antibiotic withdrawal periods on smallholding, peri-urban pig farms in Kiambu County, Kenya - Scott, C.; Bor, Nicholas; Reyher, K.K.; Tasker, A.J.; Buller, H.; Bueno, I.; Thomas, Lian F. (2025)
Non-conformance with antibiotic withdrawal period guidelines represents a food safety concern, with potential for antibiotic toxicities and allergic reactions as well as selecting for antibiotic resistance. In the Kenyan domestic pig market, conformance with antibiotic withdrawal periods is not a requirement of government legislation and evidence suggests that antibiotic residues may frequently be above recommended limits. In this study, we sought to explore enablers of and barriers to conformance with antibiotic withdrawal periods for pig farms supplying a local independent abattoir in peri-urban Nairobi. We drew upon semi-structured interviews with farmers and government animal health professionals as well as focus groups which involved private animal health professionals. We also explored farmers’ engagement with antibiotic withdrawal periods by visiting thirteen pig farms (supplying one of two local independent abattoirs) weekly for one month in order to capture instances of antibiotic use. We analysed data using reflexive thematic analysis. All farmers participating in the study demonstrated an awareness of the concept of antibiotic withdrawal periods and described intentions to conform, motivated by caring for others, wanting to prevent harm or a perception that regulation around antibiotic withdrawal periods existed for local independent abattoirs. The antibiotic use practices that we identified showed limited opportunities for non-conformance with antibiotic withdrawal periods. Farmers and veterinarians reported that instances of antibiotic use were uncommon, especially in slaughter-weight pigs, and were mainly restricted to the treatment of clinical signs under the supervision of an animal health professional. Local factors presented barriers to antibiotic withdrawal period conformance including farmers’ economic constraints, lack of formal medicine recording, an absence of consistent abattoir monitoring and resource emergency, such as water scarcity on farms. This study demonstrates the importance of these contextual factors to conformance with antibiotic withdrawal periods. We highlight the need to account for farm-level influences when planning future research and interventions aimed at reducing the presence of antibiotic residues in meat from smallholding pig farms in peri-urban Nairobi.